The nexus between digital finance and carbon emissions: Evidence from China - Cai, Xuesen; Song, Xiaowei (Frontiers in Psychology, 2022)
Finance is significant support for the low-carbon transformation of the real economy, in which digital finance as a new direction of financial development exerts a significant influence on carbon emissions. Therefore, it is crucial to investigate the association between digital finance and carbon emissions in order to develop carbon reduction strategies from the financial side. For this purpose, using the sample set covering 30 provincial areas during 2011–2020, this paper investigates the direct, indirect, and non-linear effects of digital finance on carbon emissions by applying fixed effects, mediating effects, and threshold effects analysis techniques. The results indicate that: (1) digital finance can significantly mitigate carbon emissions at the national level. (2) Digital finance inhibits carbon emissions as it drives green technological innovation and industrial structure upgrading. (3) Significant regional heterogeneity is observed in the effect of digital finance on carbon emissions, i.e., the effects of digital finance on carbon emissions are higher in the east-central region than in the overall sample, while the opposite is true in the western region. (4) The dampening effect on carbon emissions steadily increases as digital finance levels cross the first and second thresholds, respectively. Based on the above considerations, policymakers shall not only develop differentiated digital finance initiatives, but shall also fully unleash carbon emission reduction potential by rationalizing and optimizing industrial layout and strengthening financial subsidies for green technology innovation.